Leader-to-leader splicing is required for efficient production and accumulation of polyomavirus late mRNAs. - Adami, G R (1989)
Polyomavirus late mRNA molecules contain multiple, tandem copies of a noncoding 57-base "late leader" exon at their 5' ends. This exon is encoded only once in the genome. Leader multiplicity arises from leader-leader splicing in giant primary transcripts, which are the result of multiple circuits of the viral genome by RNA polymerase II. We have been interested in learning more about the role of the leader exon in late viral gene expression. We recently showed that an abbreviated-leader mutant virus (ALM) with a 9-base leader exon is nonviable (G. R. Adami and G. G. Carmichael, Nucleic Acids Res. 15:2593-2610, 1987) and has a severe defect in both late pre-mRNA splicing and stability. However, a mutant virus with a different, substituted leader sequence of 51 nucleotides (SLM/MP8) is viable and has no apparent defects. Here we examined further the role of the late leader exon in late pre-mRNA processing. When the leader exon length was gradually reduced from 51 nucleotides to 9 nucleotides in a series of mutants, RNA splicing and stability defects were coupled. In this system there was a minimum exon size of between 33 and 27 nucleotides. Next, a number of mutations were introduced into the 3' splice site which precedes the late leader. Such mutations blocked leader-leader splicing. Surprisingly, they also interfered with leader-mVP1 body splicing and resulted in unstable primary transcripts. Thus, polyomavirus leader-leader splicing appears to be important for the efficient accumulation of late viral mRNA molecules.